Exploring Students’ Academic Performance, Motivational Orientation and Self-Regulated Learning Strategies towards Chemistry - Cascolan, Honelly Mae Segui (International Journal of STEM Education for Sustainability, 2023)
Chemistry is considered one of the most difficult subjects for college students. Process Oriented Guided Inquiry Learning activities are a student-centered teaching-learning strategy used in classrooms to improve students' academic performance. This study investigates the effectiveness of POGIL activities in teaching Chemistry in the two sections of Bachelor of Industrial Technology (BIT) students enrolled in Chemistry for the first semester of 2022-2023 to determine the academic performance, motivational orientation, and self-regulated learning strategies before and after the intervention. We administered the examination on Stoichiometry and Chemical Equations and Motivated Strategies for Learning Questionnaires before and after the intervention. BIT 1B had the POGIL activities for Stoichiometry, while BIT 1A had the traditional lecture on the same topic. For the second topic, chemical equation, the intervention was switched. BIT 1A had the POGIL activities, while BIT 1B had the traditional lecture. The result showed that most respondents were male since Industrial Technology is a male-dominated course. A significant difference was observed between the post-test scores of the students exposed to POGIL activities and traditional lectures. A significant difference was also observed in the motivational orientation and self-regulated learning strategies after exposure to POGIL activities. Students in a POGIL class perform better than students in a traditional class. It is recommended to use a student-centered teaching strategy such as POGIL, which encourages active learning in teaching Chemistry to improve students' academic performance.